2020
DOI: 10.1111/gcb.15194
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation‐drainage cycles lead to hot moments in soil carbon dioxide dynamics in a Neotropical wet forest

Abstract: Soil CO 2 concentrations and emissions from tropical forests are modulated seasonally by precipitation. However, subseasonal responses to meteorological events (e.g., storms, drought) are less well known. Here, we present the effects of meteorological variability on short-term (hours to months) dynamics of soil CO 2 concentrations and emissions in a Neotropical wet forest. We continuously monitored soil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…Emissions of CO2 were associated with temperature, although the correlation was not significant, meaning that differences in temperature within season would affect emissions. Highest CO2 emissions from all land-use types during the early wet season could be attributed to "Birch effect" which refers to short term but a substantial increase of respiration from soils under the effect of precipitation during early wet season (Fernandez-Bou et al, 2020). These findings are in accordance with recent studies which reported that CO2 fluxes from subtropical mangroves were largest when the temperature was highest, and in periods of the year with reduced salinity (Liu and Lai 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Emissions of CO2 were associated with temperature, although the correlation was not significant, meaning that differences in temperature within season would affect emissions. Highest CO2 emissions from all land-use types during the early wet season could be attributed to "Birch effect" which refers to short term but a substantial increase of respiration from soils under the effect of precipitation during early wet season (Fernandez-Bou et al, 2020). These findings are in accordance with recent studies which reported that CO2 fluxes from subtropical mangroves were largest when the temperature was highest, and in periods of the year with reduced salinity (Liu and Lai 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, we observed a significant parabolic relationship between R s and soil moisture at both timescales, highlighting the importance of water availability as a regulator of biological activity in the soil, as well as soil-atmosphere gas exchange. Similar to observations in other tropical moist and wet forests, the highest rates of R s occurred during periods of intermediate soil moisture (Chambers et al, 2004;Fernández-Bou et al, 2020;Nottingham et al, 2020;Rubio & Detto, 2017;Schwendenmann et al, 2003;Sotta et al, 2004;Wood et al, 2013). At both daily and monthly timescales, the optimal soil moisture for R s was ~ 0.350 m 3 m -3 , which matches the threshold values determined at other tropical forests with similarly textured soils Sotta et al, 2004;Wood et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…In fact, daily mean R s values lower than 4 μmol CO 2 m ‐2 s ‐1 were only observed when soil moisture was higher than 0.370 m 3 m ‐3 , during periods when soil–atmosphere gas exchange was most likely limited. This negative response of R s to large precipitation events has also been documented in other tropical forests, and may be caused solely by the physical diffusion barrier created by high levels of soil moisture and/or the microbial response to reduced soil oxygen concentrations (Fernández‐Bou et al., 2020; Schwendenmann et al., 2003; Silver et al., 1999; Sotta et al., 2004; Wood et al., 2013). Further study is needed to ascertain which of the various possible controls dominate the observed response.…”
Section: Discussionmentioning
confidence: 71%
“…By relating the soil Fe redox cycling rate to hydroclimatic fluctuations, for which data are readily available (Fick & Hijmans, 2017), this analysis also paves the way for a global identification of hot spots of potential Fe reduction, in which climatic features are highly favorable and for prediction of future trends in organic matter decomposition (e.g., Fernandez‐Bou et al, 2020). The connection between the soil moisture dynamics and the oxic/anoxic cycles, presented here, could also be exploited in the context of other metabolisms (by adjusting k R and k O ) to investigate how various hydrologic regimes may promote the utilization of different electron acceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Fe reduction, in which climatic features are highly favorable and for prediction of future trends in organic matter decomposition (e.g., Fernandez-Bou et al, 2020). The connection between the soil moisture dynamics and the oxic/anoxic cycles, presented here, could also be exploited in the context of other metabolisms (by adjusting k R and k O ) to investigate how various hydrologic regimes may promote the utilization of different electron acceptors.…”
Section: 1029/2020jg005894mentioning
confidence: 95%